2019
DOI: 10.1080/15459624.2019.1648814
|View full text |Cite
|
Sign up to set email alerts
|

Passive personal air sampling of dust in a working environment—A pilot study

Abstract: The aim of this study was to make a preliminary evaluation of the University of North Carolina passive aerosol sampler (UNC sampler) for personal air sampling of particles. Nine personal air samplings of respirable fraction were conducted in an open-pit mine, with pairwise UNC samplers and a respirable cyclone mounted on the chest of workers. UNC samples were analyzed with scanning electron microscopy (SEM) and to some extent energy dispersive X-ray spectroscopy (EDS). Respirable cyclone filter samples were we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Passive samplers, which rely on less invasive technologies such as adsorbent strips and wearables like silicone wristbands, pouches, and badges, provide an alternative strategy to screen for both known and unknown exposures in large populations. PSDs validated for exposures with known uptake rates, such as benzene or trichloroethylene, have been widely used in occupational monitoring studies for industrial chemicals [23,[48][49][50][51][52][53][54]. However, for most PSDs, ongoing research is focused on better understanding the mechanisms for chemical equilibrium with sampler matrices, which can vary by chemical molecular weight, media pore size, and silicone/air partitioning coefficients [55].…”
Section: Measuring the External Exposomementioning
confidence: 99%
“…Passive samplers, which rely on less invasive technologies such as adsorbent strips and wearables like silicone wristbands, pouches, and badges, provide an alternative strategy to screen for both known and unknown exposures in large populations. PSDs validated for exposures with known uptake rates, such as benzene or trichloroethylene, have been widely used in occupational monitoring studies for industrial chemicals [23,[48][49][50][51][52][53][54]. However, for most PSDs, ongoing research is focused on better understanding the mechanisms for chemical equilibrium with sampler matrices, which can vary by chemical molecular weight, media pore size, and silicone/air partitioning coefficients [55].…”
Section: Measuring the External Exposomementioning
confidence: 99%
“…Repeated analyses over nine sessions and seven different mounts agreed within analytical uncertainty for zircons Temora 2, FC1, R33, QGNG, Plešovice and 91500 when normalised to Mud Tank zircon, which was regarded as a useful QC material with typical repeatability of #0.3& (2SD). Caution was sounded when using other zircons from the Duluth Complex (FC1, AS57 and AS3) as RMs for this purpose as they had an excessive scatter of d 18 O values associated with low-U zircon grains. Yang et al 229 assessed the O isotope homogeneity of six well-known apatite RMs and two in-house apatites by SIMS.…”
Section: Reference Materials and Data Qualitymentioning
confidence: 99%
“…A comparison of dry deposition samplers, based on 17 single-particle SEM characterisation of collected dust, concluded that differences in deposition rates between sampler types did indeed exist. A side-by-side comparison exercise, in which passive UNC samplers were worn by mine workers alongside pumped respirable air samplers as reference, demonstrated 18 that there was a ca. 30-fold over-estimation of sampled particle mass.…”
Section: Air Analysismentioning
confidence: 99%
See 1 more Smart Citation